The Effects of Solvation Enthalpy, Surface Tension, and Conductivity of Common Additives on Positive Electrospray Ionization in Selected Pharmaceuticals - Pieter Venter (Molecules)
This study investigates the effects of common additives, which provide distinct proton sources—ammonium (NH4+) and hydronium (H3O+)—along with their corresponding conjugate base species, on signal intensity in positive ionization mode. The findings reveal that signal intensity is influenced by factors such as solvation enthalpy, surface tension, and conductivity. At lower additive concentrations (<10 mM), based on fold changes, no clear distinction could be made between formic acid, acetic acid, and their corresponding salts. At higher additive concentrations, NH4+ appears to be a more efficient proton source than H+ (H3O+), likely due to its more positive solvation enthalpy, which promotes greater enrichment of NH4+ on the droplet surface, as well as the reduced surface tension of ammonium salts compared to their acid counterparts. Additionally, ammonium hydroxide proves to be the most effective ammonium-based modifier, likely due to its anionic conjugate base, hydroxide, which has a more negative solvation enthalpy compared to acetate and formate. This characteristic is hypothesized to reduce charge neutralization of cations on the droplet surface and/or in the gas phase. Furthermore, ammonium hydroxide exhibits lower conductivity compared to the other ammonium additives, which is believed to enhance signal intensity. Ammonium bicarbonate, the second most effective additive, uniquely prevents metal adduct formation, leading to enhanced [M + H]+ ion signals.